Electrical Control of Perpendicular Magnetic Anisotropy and Spin‐Orbit Torque‐Induced Magnetization Switching - Huang, Qikun; Dong, Yanan; Zhao, Xiaonan; Wang, Jing; Chen, Yanxue; Bai, Lihui; Dai, Ying; Dai, Youyong; Yan, Shishen; Tian, Yufeng (Advanced electronic materials, 2020)
Voltage‐driven oxygen ion migration in ferromagnetic metal/oxide heterostructures offers a highly effective means to tailor emergent interfacial functionalities. In heterojunctions with a core structure of Pt/Co/CoO/TiO2 (TaOx), it is demonstrated that exchange coupling of magnetic moments across the Co/CoO interface provides an extra source to stabilize the perpendicular magnetic anisotropy (PMA). Moreover, the strength of this interfacial coupling can be reversibly controlled through voltage‐driven oxygen ion migration at the Co/CoO interface, resulting in electrical‐field‐controllable PMA. In combination with the spin current generated from Pt, it is revealed that the spin‐orbit torque (SOT) switching of the perpendicular magnetization of Co can be turned ON/OFF by electrical field. Tunable PMA and SOT switching makes heavy metal/ferromagnetic metal/antiferromagnetic oxide heterojunctions a promising candidate to future voltage‐controlled, ultralow‐power, and high‐density spintronics devices. Electrical field control of perpendicular magnetic anisotropy (PMA) and spin‐orbit torque‐induced magnetization switching are reported in Pt/Co/CoO/oxide hybrid heterostructures. The exchange coupling across the Co/CoO interface provides an extra source to stabilize the PMA. Moreover, the strength of this interfacial coupling can be reversibly controlled through voltage‐driven oxygen ion migration at the Co/CoO interface, resulting in electrical‐field‐controllable PMA.